2002
DOI: 10.1152/ajpgi.00454.2001
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of hypothermic protection against ischemic liver injury in mice

Abstract: Mechanisms of hypothermic protection against ischemic liver injury in mice. Am J Physiol Gastrointest Liver Physiol 282: G608-G616, 2002. 10.1152/ajpgi.00454.2001.-Hepatic hypothermia can safely prolong the duration of hepatic inflow occlusion during complex liver resectional surgeries. The mechanism(s) by which hypothermia protects against this form of liver ischemia-reperfusion injury are not completely understood. In this study, we sought to determine whether hypothermia protects against ischemia-reperfusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
33
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 36 publications
6
33
0
1
Order By: Relevance
“…In a mouse model of 90 min of partial hepatic ischemia performed at either 37°C or ±25°C, neutrophil influx at 8 h of reperfusion was reduced by 99% in the hypothermic group. A similar extent of immunosuppression was observed in both hypothermic groups of a rat study comparing 45 min of partial hepatic ischemia at 37°C, 34°C and 31°C, thereby confirming that per-ischemic hypothermia can suppress the I/R immune response (26,42).…”
Section: Hypothermia and Immunomodulationsupporting
confidence: 69%
See 3 more Smart Citations
“…In a mouse model of 90 min of partial hepatic ischemia performed at either 37°C or ±25°C, neutrophil influx at 8 h of reperfusion was reduced by 99% in the hypothermic group. A similar extent of immunosuppression was observed in both hypothermic groups of a rat study comparing 45 min of partial hepatic ischemia at 37°C, 34°C and 31°C, thereby confirming that per-ischemic hypothermia can suppress the I/R immune response (26,42).…”
Section: Hypothermia and Immunomodulationsupporting
confidence: 69%
“…To explain this phenomenon, mRNA and serum levels of the neutrophil chemoattractants tumor necrosis factor ( TNF)-α and chemokine (C-X-C motif) ligand 2 (CXCL2) were measured in the aforementioned mouse model, which were all reduced in mice subjected to I/R under hypothermic conditions (40,42). It was additionally shown that mice exposed to hypothermic I/R had reduced activation of the protein kinase c-jun N-terminal kinase (JNK) and the transcription factor activator protein 1 (AP-1), the latter of which is known to encode a host of I/R-pertinent cytokines (18,42).…”
Section: Hypothermia and Immunomodulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies suggest that hypothermia reduces liver injury [164], [165] and [166], but it may impair liver regeneration [167]. Further research will be needed to clarify these issues.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%